The Effect of Relational e-HRM Practices on Employee Productivity Through Employment Performance on Hospital Employees in Bandung - Yoki Muchsam; Willy Arafah; Deasy Aseanty; Bahtiar Usman (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The study aims to analyze the impact of relational e-HRM practices that are a starting factor in efforts to improve productivity through performance on hospital employees in Bandung. This research method uses a quantitative approach, data collected using a questionnaire. A sample of 300 randomly selected hospital staff in Bandung during the Covid-19 pandemic. Structural Equation Model (SEM) method covariance is used to analyze data. The type of research is the testing of causal hypotheses with cross sectional data. The results show that changes in employee productivity can be predicted by changes in employee performance. Relational e-HRM practices have a positive influence on employee performance. The resulting managerial implications, the healthcare personnel in hospitals as the leading guards have improved employee productivity as the hospital governance system changes. Strict health protocols, a combination of stress, keeping distance in pandemic times is a challenge for health workers. Efforts to improve employee performance and the success of some e-HRM systems in facing obstacles are met. Leaders need to understand the situation of service change. The understanding from the employee's perspective of the health care system that can improve employee performance is improving.